Investigating the Pre-Service Teachers’ Assessment Literacy in different fields and Self-Efficacy in terms of Assessment Literacy - Çambay, Öznur; Kazanç, Sefa (Fırat University, 2018)
In this study utilizing the survey method, pre-service science, elementary and pre-school teachers’ assessment literacy and self-efficacy about assessment literacy were investigated. The relationships between pre-service teachers’ assessment literacy and self-efficacy about assessment literacy were also investigated. 105 4th grade preservice science teachers in the Department of Science Education Program (N=35), Elementary Teacher Education Program (N=35) and Pre-School Teacher Education Program (N=35) in Faculty of Education during 2015-2016 academic year participated in this study. The questionnaires and semi-structured individual interviews used to define the pre-service teachers’ assessment literacy and self-efficacy about assessment literacy. Multivariate Analysis of Variance (MANOVA) and Pearson Correlation were used to evaluate the data obtained from the result of this study in order to investigate the pre-service teachers’ assessment literacy and self-efficacy about assessment literacy. The statistical analyses of data revealed that there were statistically significance differences among the pre-service science, elementary and pre-school teachers as regards to the levels of assessment literacy and selfefficacy about assessment literacy (p<0.05). Furthermore, it was determined that there was no statistically significant correlation between assessment literacy and self-efficacy about assessment literacy of pre-service science, elementary and pre-school teachers (p> 0.05). The qualitative data obtained in the present study also supported the obtained quantitative data.

Bu çalışmada,  öğretmen adaylarının değerlendirme okuryazarlıkları ve değerlendirme okuryazarlığına ilişkin öz-yeterlikleri tarama metodu kullanılarak araştırılmıştır. Ayrıca, bu araştırmada öğretmen adaylarının değerlendirme okuryazarlıkları ve değerlendirme okuryazarlığına ilişkin öz-yeterlikleri arasındaki ilişkiler de incelenmiştir. Bu çalışmaya, 2015-2016 öğretim yılı Fırat Üniversitesi Fen Bilgisi, Sınıf ve Okul Öncesi Öğretmenliği programı dördüncü sınıfta öğrenim gören 35’er kişilik toplamda 105 öğretmen adayı katılmıştır. Araştırmada veri toplama aracı olarak, anketler ve bireysel yarı-yapılandırılmış mülakatlar kullanılmıştır. Öğretmen adaylarının değerlendirme okuryazarlıklarını ve değerlendirme okuryazarlığına ilişkin öz-yeterlik algılarını belirlemek için çalışma sonucunda elde edilen verilere Çok Değişkenli Varyans Analizi (MANOVA) ve Pearson Korelasyon analizi uygulanmıştır. Yapılan istatistiksel analizler sonucunda, öğretmen adaylarının değerlendirme okuryazarlıkları ve değerlendirme okuryazarlıklarına ilişkin öz-yeterlikleri arasında anlamlı bir farklılığın olduğu tespit edilmiştir (p<0.05). Ayrıca fen bilgisi, sınıf ve okul öncesi öğretmen adaylarının değerlendirme okuryazarlığı ve değerlendirme okuryazarlığına ilişkin öz-yeterlikleri arasında istatistiksel olarak anlamlı bir ilişkinin olmadığı belirlenmiştir (p>0.05). Bu araştırma kapsamında elde edilen nitel verilerin de nicel verileri desteklediği görülmüştür.
Farklı Branşlardaki Öğretmen Adaylarının Değerlendirme Okuryazarlığı ve Değerlendirme Okuryazarlığına İlişkin Öz-Yeterliklerinin İncelenmesi*